(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Given and n points (node) in , the Hermite-Fejer type (HFT) interpolation polynomial is the polynomial of degree at most (2n-1) that agree with and has zero derivative at each of the nodes. The aim of this paper is to investigate HFT interpolation polynomial of n such that n is an even number of Chebyshev of the first kind. Mathematics Subject classification: 2010 primary 41A05, Secondary 41A10